The Effectiveness Relaxation Therapy Of Imagination Guided Reduction Blood Pressure On Elderly With Hypertension In The Working Area Health Center Purwodadi 1 Grobogan Regency - Lufianti, Anita; Sutrisno, Sutrisno (Universitas Muhammadiyah Semarang, 2019)
The disease of hypertension called The Silent Diseases. At least 970 people in the world have hypertension. Every years more than 8.6 million woman die on global scale caused stroke and heart disease. In Indonesia, estimated 15 million hypertension people. The purpose of this research is To determine the effectiveness of relaxation guided imagination therapy to decrease blood pressure on hypertension eldery. This is a research of Quasi Experiment approach Non Equivalent Control Group Design. With a population of elderly patients 65-74 years old, female and suffering from hypertension grade 1 (140/90mmHgâ€“159/99mmHg). Which runs farmakologi antihypertensive therapy. 84 samples collected by sampling purposive. The Result : There are significant differences on blood pressure pretest and posttest of treatment group (p value=0.000). There are significant differences on blood pressure pretest and posttest of control group (p value=0.000). There are significant differences on blood pressure between treatment group with control group (p value=0.000). With an average reduction blood pressure systole on treatment group =59.31mmHg, on control group =25.69mmHg, the difference =33.61mmHg. Reduction blood pressure dyastole avarage on treatment group =57.43mmHg, on control group =27.57mmHg with an avarage =29.86mmHg. Relaxation guided imagination therapy effective to decrease blood preassure in elderly with hypertension in the working area Health Center Purwodadi Â Purwodadi sub-district Grobogan Regency.